Enfoques Teóricos Metodológicos de J.B. Thompson em Pesquisas da Psicologia Social - Ribeiro, Maria Silvia (2022)
This work is an integral part of the research line “Contributions of Social Psychology to the understanding of social problems”, of the Postgraduate Program in Social Psychology at the Pontifical Catholic University of São Paulo, together with the Center for Gender, Race and Age Studies. Many of our studies are supported by John B. Thompson’s theory of ideology (2011), focused on the search for understanding the axes of  inequalities and are interested in apprehending the ways in which symbolic forms intersect with power relations. In this writing, we present John B. Thompson’s contributions on ideology and power relations, considering that they prepare the way, both theoretically and historically, for the dialogue with the fields ofstudies adopted in our collective research.